Litotetothrips Priesner (Thysanoptera, Phlaeothripinae); an Asian genus newly recorded from Australia with two new species and one new combination - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2021)
Relationships are discussed among the five genera related to Liothrips in which species have antennal segment VIII long and slender. Litotetothrips is the oldest of these generic names and is used here for three species newly recorded from Australia: L. caledonensis (Bournier) comb.n., L. gallicola sp.n. and L. tareei sp.n.